Development of a chemically defined medium for Yarrowia yeasts using a strategy of biological mimicry - Oliver Birrenbach; Peter Czermak (Electronic Journal of Biotechnology)
Background: The efficiency of recombinant protein production in Yarrowia lipolytica is strongly influenced by the culture medium. Complex media have limited applications because the composition is undefined and variable, whereas chemically defined media achieve better yields and reproducibility. Defined media also increase selectivity, reduce contamination risks, and enable precise nutrient control, leading to better growth and higher productivity. We used a design of experiments approach based on the elemental composition of yeast for the arithmetic development and optimization of a defined medium for the Y. lipolytica auxotrophic strain PO1f. Results: Statistically supported optimal concentrations of 10 g*L−1 glucose and 2.29 g*L−1 leucine enabled superior growth in the new in silico yeast (ISY) medium. Specific growth rates of 0.305 h−1 were achieved for the auxotrophic Yarrowia strain. Thiamine hydrochloride was a growth-limiting component, and higher concentrations increased the cell density of Y. lipolytica PO1f cultures by a factor of 30. Conclusions: ISY medium was suitable not only for the cultivation of Y. lipolytica but also universally applicable for Yarrowia-like and other yeasts, achieving better growth rates and yields compared to existing chemically defined media.How to cite: Birrenbach O, Czermak P. Development of a chemically defined medium for Yarrowia yeasts using a strategy of biological mimicry. Electron J Biotechnol 2025;73. https://doi.org/10.1016/j.ejbt.2024.10.001.